Relationship Between Health and Economic Growth in India. Issue 3 (December 2019) - Verma, C. S.; Usmani, Gulnawaz
This study employs the Granger causality test to investigate the relationship between health and economic growth in India. The annual data of major 15 states on infant mortality rate (IMR) and gross state domestic product (GSDP) from 1985 to 2015 is studied and analysed. The main finding of the study is that there is bilateral causality between GSDP and IMR. However, while testing the null hypothesis for each state, study finds the evidence of unilateral causality also, which is either running from IMR to GSDP and/or GSDP to IMR. With existence of such relationship, it is recommend that government should focus on the healthcare sector to achieve a higher rate of economic growth.